Trends in Body Mass Index among Icelandic Adolescents and Young Adults from 1992 to 2007 - Eiðsdóttir; Kristjánsson; Sigfúsdóttir; Garber; Allegrante (International Journal of Environmental Research and Public Health, 2010)
Trends in body mass index (BMI) among 51,889 14- to 20-year-old Icelandic adolescents and young adults were examined using data from cross-sectional population surveys conducted from 1992 to 2007. Prevalence of overweight increased for both genders in all age groups, except for 14- and 20-year-old girls. Obesity prevalence increased among boys in all age groups, except for 16-year-olds, and among 15- and 20-year-old girls. The largest increase in obesity rates among both genders was found in the oldest age group. Moreover, not only has the prevalence of obesity increased, but also the extent of obesity has grown more severe among 15- and 17-year-olds boys and among girls in the oldest age group.